PROGRAM FOR IMPROVING THE UNDERSTANDING OF TYPES OF DENTAL RESTORATION - Firdausy, Muhammad Dian; Hadianto, Eko; Mayangsari, Regilia Shinta; Nurazky, Savira; Indrawati, Silvia Vera; Putra Pratama, Muhammad Dimas (Faculty of Dentistry Universitas Islam Sultan Agung, 2024)
Background: Dental and oral health is an important part of overall body health. Cavities are one of the most common dental and oral problems experienced by people in the world, including in Indonesia. Cavities must get treatment as soon as possible before causing unwanted things. The increasing and growing use of filling materials is in line with increasing public awareness of dental and oral health. However, this is not evenly distributed in all regions, only areas that have adequate access and technology can reach this information, so education efforts are needed for people outside the area. Health education is one of the efforts to increase knowledge, attitudes, and good practices in individuals, groups, or communities in maintaining and improving public health. The locations that are targeted in this community service are villages in the working area of the Margasari Health Center, Tegal Regency, Central Java.Method: The planned educational activities include surveying the problems encountered, counseling and discussions on the topic of introducing dental fillings in children and adults. This community service aims to increase public awareness of the importance of treating cavities and increase public understanding regarding the choice of materials used in the treatment of cavities. Result: Counseling begins by distributing questionnaires before and after the counseling. The selected counseling material is material about various additives commonly used in dentistry. The data was then entered and it was found that there was a significant difference between before and before the research was carried out, the p-value was 0.000.Conclusion: The education provided through counseling can be concluded as effective in increasing the knowledge of the people of Margasari Village.